2011
DOI: 10.1007/s10549-010-1161-z
|View full text |Cite
|
Sign up to set email alerts
|

FOXO3a nuclear localisation is associated with good prognosis in luminal-like breast cancer

Abstract: In this study, we investigated the clinical relevance and biological associations of FOXO3a protein expression, using tissue microarrays and immunohistochemistry, in a large series of patients with invasive breast cancer.FOXO3a protein expression showed both nuclear and/or cytoplasmic staining patterns. FOXO3a predominant nuclear expression was positively associated with biomarkers of good prognosis including PgR, FOXA1, and p27 expression. There was an inverse association with mitotic counts, MIB1 growth frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 39 publications
8
57
1
1
Order By: Relevance
“…S1B). These data are corroborated by IHC data from other laboratories for normal breast and tumor tissues Habashy et al, 2011;Hu et al, 2004). pFoxO3a T32, indicative of inactive FoxO3a, was elevated ,50% above that of adjacent normal thyroid tissue and was cytoplasmic (supplementary material Fig.…”
Section: Foxo3a Localization and Akt Activity In Atc Cellssupporting
confidence: 81%
“…S1B). These data are corroborated by IHC data from other laboratories for normal breast and tumor tissues Habashy et al, 2011;Hu et al, 2004). pFoxO3a T32, indicative of inactive FoxO3a, was elevated ,50% above that of adjacent normal thyroid tissue and was cytoplasmic (supplementary material Fig.…”
Section: Foxo3a Localization and Akt Activity In Atc Cellssupporting
confidence: 81%
“…Consistent with this, decreased expression of FOXO3a associated with poor outcomes in breast cancer and neuroblastoma (Sunayama et al 2011;Jiang et al 2013;Santo et al 2013). Conversely, FOXO3a nuclear localization is associated with good prognosis in luminal-like breast cancer (Habashy et al 2011). Moreover, exogenous expression of FOXO3a inhibits tumor growth in vitro and in vivo in breast cancer (Hu et al 2004;Yang et al 2008;Lin et al 2011;Sisci et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have shown that FOXO3a could serve as an independent predictor for survival in these cancers Fei et al 2009;Habashy et al 2011;Shiota et al 2010;Shi et al 2009). However, with regard to the possible role of FOXO3a on NPC patients' prognosis, it is still unclear thus far.…”
Section: Discussionmentioning
confidence: 99%
“…However, phosphorylation of FOXO3a by PI3K/Akt enhances its interaction with 14-3-3 protein and promotes FOXO3a nuclear export to cytoplasm, resulting in its ubiquitination and proteasomal degradation, thereby blocking its activity (Brunet et al 1999). Emerging evidences suggest that aberrant expression of FOXO3a is associated with hepatocellular carcinoma ), ovarian cancer (Fei et al 2009), breast cancer (Habashy et al 2011), urothelial cancer (Shiota et al 2010, and thyroid cancer (Karger et al 2008). These results suggest that FOXO3a may play a crucial role in the development and progression of human cancers.…”
Section: Introductionmentioning
confidence: 99%